Diagnostic imaging : brain - Osborn, Anne G (AMIRSYS, 2004)
Reach a more accurate diagnosis more efficiently than ever. This new Diagnostic Imaging text in a unique new format offers luminary authorship, about 250 diagnoses, with sample images to introduce each diagnosis, DDx images demonstrate alternative diagnostic possibilities and Image Galleries show a range of typical imagining findings.
Keywords: Diagnosis, Differential; diferenciální diagnóza; Neuroradiography; neurovědy; Brain; radiologie, nukleární medicína a zobrazovací metody; mozek; neurologie; neuroradiografie